Influence of Surface Pretreatments on the Anticorrosion of Polypyrrole Electro-Polymerized Coatings for Copper in Artificial Seawater - Hetao Zhu; Xiaoyan Liu; Hua Hao; Xingwen Zheng (Metals, 2022)
Plasma discharging treatment (hydroxylation) was conducted on copper surfaces for the subsequent electro-polymerization procedure of polypyrrole (PPy) coating (d-PPy). The hydroxylated surface could solve the criticized adhesion strength and protection efficiency of electropolymerized coatings for metal substrate in corrosive media. Compared with the counterpart obtained via passivation pretreatment (p-PPy), a well-adhered d-PPy layer was acquired on the hydroxylated copper surface, which earned a satisfactory adhesion grade, compactness and conductivity. Appreciable protection of d-PPy was measured for copper in the artificial seawater (ASW) at 298 K via electrochemical and surface analyses. Results of electrochemical measurements indicated that d-PPy coating effectively retarded copper corrosion in ASW with a lowered corrosion current density and improved charge transfer resistance. Surface analysis revealed that the typical morphology of PPy was retained after 240 h immersion in ASW. A favorable physical barrier and anodic protection efficacy might account for the superior protection of d-PPy coating for the underlying copper. Molecular dynamics simulations for the deposition of PPy chains on pristine and hydroxylated copper planes provided a definite correlation between the theoretical calculations and experimental observations. Theoretical modelling also disclosed in-depth the anchoring nature and anticorrosive mechanism for PPy toward the hydroxylated copper in ASW.